Histological assessment of ovaries and uterus of rats subjected to nandrolone decanoate treatment - Gerez, JR; Frei, Fernando [UNESP]; Camargo, ICC (Elsevier B.V., 2005)
This study aimed to analyze the effects of nandrolone decanoate on the ovaries and uterus of adult females rats. This drug was administered intraperitoneally, at one, two and three doses of 3 mg nandrolone decanoate/kg of body weight, respectively, in the first, second and third week of treatment. The females of the control group received a physiological solution. The rats treated with nandrolone decanoate showed estral acyclicity and there was destruction of follicular units and an absence of corpus luteum in the ovaries. In the uterus, the drug promoted morphological alterations, characterized by vacuolated epithelium and endometrial stroma fibrosis. Ovary, uterus and pituitary weights were not affected by the steroid treatment. Nandrolone decanoate affects the sexual cycle and promotes histological alterations in the ovaries and uterus of adult female rats. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: nandrolone decanoate; ovaries; uterus; histology; adult female rats